Forecasting particulate matter concentration using linear and non-linear approaches for air quality decision support - Abdullah S.; Ismail M.; Ahmed A.N.; Abdullah A.M. (MDPI AG, 2023)
Air quality; Decision support systems; Fog; Forecasting; Functions; Linear regression; Nonlinear systems; Particles (particulate matter); Radial basis function networks; Forecasting algorithm; Forecasting performance; Malaysia; Multi layer perceptron; Multiple linear regressions; Particulate Matter; Radial basis functions; Urban and rural areas; Urban growth; air quality; algorithm; decision support system; early warning system; forecasting method; multiple regression; particulate matter; performance assessment; precision; Malaysia; West Malaysia